Preparation process of high-performance environment-friendly magnesium aluminate spinel refractory material

By using high-purity magnesium sand, activated alumina powder and bauxite clinker, combined with nano-grade titanium oxide and rare earth oxide additives, the preparation process is optimized, and the problems of insufficient performance and environmental protection in the high-temperature industry are solved, and the preparation of high-performance, environmentally friendly and energy-saving refractory materials is achieved.

CN119707454APending Publication Date: 2025-03-28NANJING IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411756228.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional refractory materials face problems such as insufficient performance, serious environmental protection problems and high production costs in the high-temperature industry. Especially in the process of steel smelting, refractory materials are easily eroded by high-temperature slag, have poor thermal shock stability, and pollutants will be generated during the production process.

Method used

High-purity magnesium sand, activated alumina powder and bauxite clinker are used as the main raw materials, combined with nano-scale titanium oxide and rare earth oxide as additives, and optimize the raw material formula and preparation process to improve the high-temperature, erosion and thermal shock stability of refractory materials, and reduce environmental pollution in the production process.

Benefits of technology

It significantly improves the high temperature resistance, corrosion resistance and thermal shock stability of refractory materials, extends the service life of the equipment, reduces maintenance costs, and achieves the goals of environmental protection and energy saving.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of a high-performance environment-friendly magnesium aluminate spinel refractory material. The preparation method comprises the following steps: raw material preparation, mixing process, molding and sintering. The magnesium aluminate spinel refractory material prepared by the invention has the characteristics of excellent high-temperature resistance, super-strong erosion resistance, excellent thermal shock resistance, remarkable environmental protection advantage, good economic and social benefits and the like; by optimizing the raw material formula and the preparation method, the high temperature resistance, erosion resistance and thermal shock resistance of the refractory material are improved, meanwhile, environmental pollution in the production process is reduced, and the requirements of high-temperature industry for high performance and environmental protection of the refractory material are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials and relates to a preparation process of a high-performance environmentally friendly magnesia-alumina spinel refractory material. Background Art

[0002] In modern high-temperature industrial fields, such as steel, nonferrous metallurgy, glass, cement and other industries, refractory materials constitute the lining of various high-temperature equipment, directly bearing the test of extreme conditions such as high temperature, chemical erosion, thermal cycle and mechanical stress. The performance of refractory materials not only determines the operating efficiency and service life of high-temperature equipment, but also greatly affects product quality and production costs; however, with the continuous advancement of industrial technology and the increasing awareness of environmental protection, traditional refractory materials have exposed many problems. On the one hand, in terms of performance, many traditional refractories are difficult to meet the increasingly stringent industrial needs; for example, in the steel smelting process, the refractories used in key equipment such as ladles and refining furnaces are often faced with strong erosion by high-temperature slag, resulting in rapid damage to the lining. Frequent maintenance and replacement not only increase equipment downtime and reduce production efficiency, but also significantly increase production costs; at the same time, some refractories have poor thermal shock stability and are prone to cracking and spalling under conditions of rapid temperature changes, further shortening their service life; on the other hand, environmental protection issues have become an important factor restricting the development of traditional refractories; some traditional refractories will produce a large amount of pollutants during the production process, causing serious harm to the environment; for example, during the use of chromium-containing refractories, chromium may be released into the environment, causing soil and water pollution, posing a potential threat to the ecological environment and human health; in addition, the energy consumption in the production process of some refractories is high, which is not in line with the concept of sustainable development.

[0003] As a refractory component with excellent performance, magnesium-aluminum spinel has good chemical stability, high melting point and excellent corrosion resistance. In theory, it is an ideal raw material for preparing high-performance refractory materials. However, the existing preparation process of magnesium-aluminum spinel refractory materials still has many shortcomings. In terms of raw material selection, the purity of some raw materials is not high enough and the impurity content is relatively high, which affects the performance of the final product. In terms of its synthesis method, traditional processes may not be able to effectively control the formation process of spinel, resulting in imperfect crystal structure, which in turn affects the overall performance of the material. The use of additives also lacks systematicity and optimization, and fails to give full play to the effect of additives on improving material performance.

[0004] Therefore, in order to adapt to the sustainable development needs of high-temperature industries, it is urgent to develop a new preparation process for magnesia-alumina spinel refractory materials to achieve environmental protection and energy-saving goals while improving material performance, so as to solve the many challenges currently faced in the refractory field. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to disclose a preparation process of a high-performance, environmentally friendly magnesia-alumina spinel refractory material. By optimizing the raw material formula and preparation method, the high temperature resistance, corrosion resistance and thermal shock stability of the refractory material are improved, while reducing environmental pollution in the production process, thereby meeting the high performance and environmental protection requirements of the high temperature industry for refractory materials.

[0006] The technical solution of the present invention is: the present invention provides a preparation process of a high-performance environmentally friendly magnesium-aluminum spinel refractory material, and the preparation steps are as follows:

[0007] Step (1), raw material preparation:

[0008] The main raw materials are high-purity magnesia (MgO content ≥ 97%, particle size of 0.5-5mm accounts for 40-50%, 0-0.5mm accounts for 10-20%), activated alumina powder (Al2O3 content ≥ 99%, particle size D0.9 ≤ 5μm) and bauxite clinker (Al2O3 content ≥ 85%, particle size of 0.5-3mm accounts for 20-30%);

[0009] The additives are nano-sized titanium oxide (TiO2 content ≥ 99.5%, particle size D0.9 ≤ 100nm) and rare earth oxides (such as lanthanum oxide La2O3 content ≥ 99%), and the addition amounts are 1-3% and 0.5-1.5% of the total mass of the raw materials respectively;

[0010] Step (2), mixing process:

[0011] The above-mentioned magnesia, activated alumina powder and bauxite clinker are added into a planetary ball mill in proportion, and a dispersant (such as sodium polyacrylate) accounting for 0.1-0.3% of the total mass of the raw materials is added at the same time, anhydrous ethanol is used as the medium, the ball-to-material ratio is 3-5:1, the rotation speed is 200-300r / min, and the ball milling time is 2-4h to obtain a uniformly mixed slurry;

[0012] Add nano-sized titanium oxide and rare earth oxide to the above slurry, and continue ball milling for 1-2 hours to make the additives evenly dispersed in the slurry;

[0013] Step (3), molding and sintering:

[0014] The mixed slurry is spray dried, and an appropriate amount of polyvinyl alcohol (PVA) solution is added to the dried powder as a temporary binder, the mass concentration of the polyvinyl alcohol solution is 5-10%, and the added amount is 3-5% of the mass of the powder; then, the powder is pressed and formed on a hydraulic press at a pressure of 100-150MPa, and the size of the green body is determined according to actual needs;

[0015] The formed green body is placed in a high-temperature sintering furnace, heated to 1600-1700°C at a heating rate of 5-10°C / min in an air atmosphere, kept at a temperature for 3-5h, and then cooled to room temperature with the furnace to obtain a finished magnesia-alumina spinel refractory material.

[0016] The beneficial effects of the present invention are: 1. Excellent high temperature resistance: high purity magnesia, activated alumina powder and bauxite clinker are used as the main raw materials, and their high purity characteristics ensure the stability of the materials under high temperature environment; by accurately controlling the particle size distribution of the raw materials, a denser structure can be formed during the sintering process, effectively reducing the presence of defects such as pores; under high temperature, this dense structure can effectively prevent the intrusion of substances such as oxygen and slag, significantly improving the high temperature resistance of the refractory material; after actual testing, its load softening temperature can be as high as 1700℃ or more, which is much higher than traditional refractory materials, and can work stably for a long time under extremely high temperature conditions, providing reliable lining protection for high temperature industrial equipment; 2. Super strong corrosion resistance Strength: The introduction of nano-sized titanium oxide and rare earth oxide additives is the key to improving corrosion resistance; during the sintering process, nano-sized titanium oxide reacts with other raw materials to form a titanate phase with high chemical stability and corrosion resistance; these titanate phases are evenly distributed in the material matrix, effectively resisting the erosion of corrosive media such as molten steel and slag; the addition of rare earth oxides optimizes the microstructure of the material, enhances the grain boundary bonding force, and makes the material more durable in the face of erosion; experiments show that the erosion rate of the refractory material prepared by the present invention is significantly lower than that of traditional refractory materials after long-term contact with molten steel and slag, which prolongs the service life of the equipment and reduces maintenance costs; 3. Excellent thermal shock stability: reasonable raw material ratio and advanced The preparation process works together to give the material excellent thermal shock stability; the good matching between the raw materials enables the thermal stress generated inside the material to be effectively dispersed and buffered when the temperature changes sharply; during the thermal shock process, the material will not show crack expansion and spalling due to the concentration of thermal stress; after multiple rigorous thermal shock cycle tests (1100℃ water cooling), the strength retention rate of the refractory material of the present invention can still reach more than 80%, while the strength retention rate of traditional refractory materials under the same test conditions is often lower; this means that in actual industrial applications, such as intermittent operation in the steel production process, the refractory material can better adapt to the working conditions of frequent temperature changes, reduce damage caused by thermal shock, and improve the continuity and stability of production; 4. Significant environmental advantages: The present invention avoids potential environmental hazards such as chromium pollution during production, use and disposal from the source; in the preparation process, anhydrous ethanol is selected as the ball milling medium. Compared with traditional organic media, anhydrous ethanol has the advantages of low volatility and low toxicity, and can be recycled through a recovery device, effectively reducing the emission of organic volatiles; in addition, the temporary binder polyvinyl alcohol can be completely decomposed during the sintering process, and no harmful substances will remain in the final product; the entire production process achieves clean production, which helps to promote the sustainable development of the refractory industry; 5. Good economic and social benefits: The high performance characteristics significantly extend the service life of the prepared refractory materials in high-temperature industrial equipment;For example, when used in ladles and refining furnaces in the steel industry, it can reduce the number of equipment repairs and replacements due to lining damage, reducing equipment downtime; at the same time, due to the excellent corrosion resistance and thermal shock stability of the material, the consumption of refractory materials is reduced; from a social perspective, environmentally friendly preparation processes help reduce the industry's negative impact on the environment, promote the rational use of resources, and promote the sustainable development of the entire high-temperature industry, which is in line with the long-term interests of social development. ; DETAILED DESCRIPTION

[0017] The specific technical scheme of the present invention is further described in detail below with reference to specific examples.

[0018] Example 1

[0019] A preparation process of a high-performance environmentally friendly magnesium-aluminum spinel refractory material, the preparation steps of which are as follows:

[0020] 1. Raw material preparation:

[0021] Take magnesia (MgO content 97.5%, 0.5-5mm accounts for 45%, 0-0.5mm accounts for 15%), activated alumina powder (Al2O3 content 99.2%, particle size D0.9 = 3μm), bauxite clinker (Al2O3 content 86%, particle size 0.5-3mm accounts for 25%);

[0022] Prepare nano-sized titanium oxide (TiO2 content 99.8%, particle size D0.9 = 80nm) and lanthanum oxide (La2O3 content 99.5%) as additives;

[0023] 2. Mixing process:

[0024] Magnesia, activated alumina powder and bauxite clinker were added into a planetary ball mill, and a sodium polyacrylate dispersant accounting for 0.2% of the total weight of the raw materials was added, anhydrous ethanol was used as the medium, the ball-to-material ratio was 4:1, the rotation speed was 250r / min, and the slurry was obtained by ball milling for 3 hours;

[0025] Add 2% of the total mass of raw materials nano-sized titanium oxide and 1% of lanthanum oxide to the slurry, and continue ball milling for 1.5 hours;

[0026] 3. Molding and sintering:

[0027] After spray drying, a polyvinyl alcohol solution with a mass concentration of 8% (the added amount is 4% of the mass of the powder) is added, and the mixture is pressed into shape at a pressure of 120 MPa on a hydraulic press.

[0028] The green body is heated to 1650°C at a rate of 8°C / min in a high-temperature sintering furnace, kept at that temperature for 4 hours, and cooled along with the furnace to obtain a finished product.

[0029] Example 2

[0030] A preparation process of a high-performance environmentally friendly magnesium-aluminum spinel refractory material, the preparation steps of which are as follows:

[0031] 1. Raw material preparation:

[0032] Magnesia (MgO content 98%, 0.5-5mm accounts for 40%, 0-0.5mm accounts for 20%), activated alumina powder (Al2O3 content 99.5%, particle size D0.9 = 2μm), bauxite clinker (Al2O3 content 87%, 0.5-3mm accounts for 20%);

[0033] Nano-sized titanium oxide (TiO2 content 99.6%, particle size D0.9 = 60nm) and lanthanum oxide (La2O3 content 99.3%);

[0034] 2. Mixing process:

[0035] The mixing process was the same as in Example 1, but the ball milling time was 2 h, and the ball milling was continued for 2 h after the additive was added;

[0036] 3. Molding and sintering:

[0037] After spray drying, a polyvinyl alcohol solution with a mass concentration of 6% was added (the amount added was 3% of the mass of the powder), and the mixture was pressed on a hydraulic press at a pressure of 100 MPa to form the mixture.

[0038] The green body is heated to 1600°C at 5°C / min in a high-temperature sintering furnace, kept at that temperature for 5 hours, and cooled along with the furnace to obtain a finished product.

[0039] Example 3

[0040] A preparation process of a high-performance environmentally friendly magnesium-aluminum spinel refractory material, the preparation steps of which are as follows:

[0041] 1. Raw material preparation

[0042] Magnesia (MgO content 97%, 0.5-5mm accounts for 50%, 0-0.5mm accounts for 10%), activated alumina powder (Al2O3 content 99%, particle size D0.9=4μm), bauxite clinker (Al2O3 content 85%, 0.5-3mm accounts for 30%).

[0043] Nano-scale titanium oxide (TiO2 content 99.7%, particle size D0.9 = 90nm) and lanthanum oxide (La2O3 content 99.4%).

[0044] 2. Mixing process:

[0045] The mixing process was the same as in Example 1, with the ball milling time being 4 h, and the ball milling was continued for 1 h after the additives were added.

[0046] 3. Molding and sintering:

[0047] After spray drying, a polyvinyl alcohol solution with a mass concentration of 10% was added (the amount added was 5% of the mass of the powder), and the mixture was pressed into shape at a pressure of 150 MPa on a hydraulic press.

[0048] The green body is heated to 1700°C at a rate of 10°C / min in a high-temperature sintering furnace, kept at that temperature for 3 hours, and cooled along with the furnace to obtain a finished product.

[0049] With the development of high-temperature industries such as steel, nonferrous metallurgy, glass, and cement, the performance requirements for refractory materials are increasing day by day. The magnesium-aluminum spinel refractory material prepared by the present invention has excellent high-temperature resistance, corrosion resistance, and good thermal shock stability, and can be widely used in key parts of the above-mentioned industries, such as ladles and refining furnaces in the steel industry, which helps to improve the service life of equipment and reduce production costs, and has broad market prospects.

Claims

1. A process for preparing a high-performance, environmentally friendly magnesium-aluminum spinel refractory material, characterized in that: The preparation steps are as follows: Step (1): raw material preparation; Step (2): mixing process; Step (3): molding and sintering.

2. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 1, characterized in that: In step (1), the raw material preparation is specifically as follows: high-purity magnesia, activated alumina powder and bauxite clinker are used as main raw materials, and nano-scale titanium oxide and rare earth oxide are selected as additives.

3. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 2, characterized in that: Among the main raw materials, high-purity magnesia: MgO content ≥ 97%, 0.5-5mm particle size accounts for 40-50%, 0-0.5mm accounts for 10-20%; The activated alumina powder has an Al2O3 content of ≥99% and a particle size of D0.9≤5μm; The bauxite clinker has an Al2O3 content of ≥85% and a particle size of 0.5-3 mm accounting for 20-30%.

4. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 2, characterized in that: In the additive, nano-scale titanium oxide: TiO2 content ≥ 99.5%, particle size D0.9 ≤ 100nm; The rare earth oxide is lanthanum oxide, and its content is ≥99%.

5. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 2, characterized in that: The addition amounts of the main raw material and additives are 1-3% and 0.5-1.5% of the total mass of the raw materials respectively.

6. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 1, characterized in that: In step (2), the mixing process is specifically as follows: the magnesia sand, activated alumina powder and bauxite clinker in step (1) are added into a planetary ball mill in proportion, a dispersant is added at the same time, anhydrous ethanol is used as a medium, the ball-to-material ratio is 3-5:1, the rotation speed is 200-300 r / min, and the ball milling time is 2-4h to obtain a uniformly mixed slurry; Add nano-sized titanium oxide and rare earth oxide to the above slurry, and continue ball milling for 1-2 hours to make the additives evenly dispersed in the slurry.

7. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 6, characterized in that: The added dispersant is sodium polyacrylate, and its added amount accounts for 0.1-0.3% of the total mass of the raw materials.

8. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 1, characterized in that: In step (3), the molding and sintering are specifically as follows: spray drying the slurry mixed in step (2), adding polyvinyl alcohol solution to the dried powder as a temporary binder; then pressing and molding on a hydraulic press, and the size of the green body is determined according to actual needs; finally, the molded green body is placed in a high-temperature sintering furnace, and heated to 1600-1700°C at a heating rate of 5-10°C / min in an air atmosphere, and the heat preservation time is 3-5h, and then cooled to room temperature with the furnace to obtain a finished magnesia-alumina spinel refractory material.

9. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 8, characterized in that: The mass concentration of the polyvinyl alcohol solution is 5-10%, and the amount added is 3-5% of the mass of the powder.

10. The process for preparing a high-performance environmentally friendly magnesium-aluminum spinel refractory material according to claim 8, characterized in that: The pressure of the hydraulic press is: 100-150MPa.